Space-time mapping of co-working spaces in Cairo: shifting paradigms from openness to technologically controlled spaces - Heba Mourad (SpringerOpen, 2021)
Abstract The paper demonstrates how co-working spaces, with their openness ideologies that are not only manifested in sharing space, but also sharing knowledge and generating access to nonhierarchical productive opportunities, are being subsumed into reinforcing neoliberal exclusiveness. The paper questions the openness of co-working spaces that reconciled with the dominant ideologies of 2011 Cairo, setting the stage to the mushrooming of co-working spaces inside Cairo’s apartment buildings as zones of relative freedom. Through space-time mapping of the emergence of co-working spaces in Cairo, in addition to interviews with co-workers, co-founders, and managers of co-working spaces, the spatial appropriation and accessibility of co-working spaces are demonstrated. Using content analysis and space syntax analysis, the study differentiates between two paradigmatic shifts in the spatial appropriation of co-working spaces—from democratizing digital infrastructure in the aftermath of 2011, to being subsumed by technological capitalist ventures by the end of 2015 into a closed paradigm, they originally emerged to defy—and compares between the spatial accessibility, visual accessibility, and social diversity of the two waves of co-working spaces. Using Cairo’s co-working spaces as a case study, this paper shows how ideologies of openness “neutral” as they may seem, can serve to legitimize exclusiveness, emphasizing how ideas—as men—can be socially located, and serve to legitimize a particular social situation.